Who adds value to ventures? Understanding the roles and relative contributions of key advisors in high-technology startups - David Y. Choi; Martin Stack (The Journal of Entrepreneurial Finance and Business Ventures, 2005)
During the process of starting and growing a company, entrepreneurs seek help from their key advisors, which include its directors, advisory board members, financiers, as well as others informally affiliated with the venture. This paper examines how the various groups add value to a venture and assesses the relative value of their contributions. Through a survey of high technology entrepreneurs, we find that directors, advisory board members and informal advisors add significant value by offering their expertise in various fields. Surprisingly, investors add relatively little value, even in such key areas as strategic planning and finance. While professional venture capitalists add more value than private investors, even the venture capitalists' contribution was perceived lower than those of the other advisors in key areas. Our results suggest that the contributions of investors may have been overestimated in conventional literature.
Keywords: 650